2000
DOI: 10.1016/s0735-1097(99)00490-8
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital ventricular fibrillation in patients with acute myocardial infarction

Abstract: Acute myocardial infarction due to occlusion in the left coronary artery (LCA) is associated with greater risk for out-of-hospital VF compared to the RCA. The location of occlusion within LCA (LAD, LCx, proximal or distal), amount of myocardium at risk for necrosis and extent of CAD are not related to out-of-hospital VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 23 publications
3
34
2
1
Order By: Relevance
“…Infarct location and culprit coronary artery were not identified as independent, significant risk factors. Recently, Gheeraert et al 7 showed that an occlusion of the left coronary artery (left anterior descending coronary artery and right circumflex artery) was associated with a greater risk of VF than an occlusion of the right coronary artery. Probably, differences in inclusion criteria and smaller sample size in the latter study explain these differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infarct location and culprit coronary artery were not identified as independent, significant risk factors. Recently, Gheeraert et al 7 showed that an occlusion of the left coronary artery (left anterior descending coronary artery and right circumflex artery) was associated with a greater risk of VF than an occlusion of the right coronary artery. Probably, differences in inclusion criteria and smaller sample size in the latter study explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…6 A large ischemic area is not associated with an increased probability of VF. 7 Site of infarction has been reported as a potential risk factor, because 2 relatively small studies showed that anterior myocardial wall infarction was more prevalent among primary VF patients than acute myocardial infarction patients without VF. 7,8 Two important epidemiological studies introduced the concept of a genetic risk factor for SCD.…”
Section: Editorial P 1134 Clinical Perspective P 1145mentioning
confidence: 99%
See 1 more Smart Citation
“…A lesion was considered the culprit if it appeared fresh on angiography and, in case of more than one lesion, if it corresponded with the location of ST elevation on the electrocardiogram. 11 Echocardiography data were gathered retrospectively. Medication use during follow-up was gathered by a written 1-year follow-up questionnaire to all PCI patients in the Academic Medical Center, Amsterdam, The Netherlands, which accounted for most of the included patients.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, the AMI mortality rate is highest during patient transfer to hospital following symptom onset, and the major cause of death is ventricular fibrillation resulting from occlusion of the IRA. 35 Thus, early reperfusion soon after symptom onset is important to reduce overall AMI mortality. In terms of prehospital thrombolysis, 36 cooperation between clinics and hospitals makes it possible to provide medical care before arriving at hospital and to reduce cardiac dysfunction and subsequently improve prognosis in the chronic phase, resulting in good quality of life.…”
Section: Discussionmentioning
confidence: 99%